Corneal collagen crosslinking for keratoconus. A review - M. M. Bikbov; V. K. Surkova (Oftalʹmologiâ, 2014)
Photochemical crosslinking is widely applied in ophthalmology. Its biochemical effect is due to the release of singlet oxygen that promotes anaerobic photochemical reaction. Keratoconus is one of the most common corneal ectasia affecting 1 in 250 to 250 000 persons. Currently, the rate of iatrogenic ectasia following eximer laser refractive surgery increases due to biomechanical weakening of the cornea. Morphologically and biochemically, ectasia is characterized by corneal layers thinning, contact between the stroma and epithelium resulting from Bowman’s membrane rupture, chromatin fragmentation in keratocyte nuclei, phagocytosis, abnormal staining and arrangement of collagen fibers, enzyme system disorders, and keratocyte apoptosis. In corneal ectasia, altered enzymatic processes result in the synthesis of abnormal collagen. Collagen packing is determined by the activity of various extracellular matrix enzymes which bind amines and aldehydes of collagen fiber amino acids. In the late stage, morphological changes of Descemet’s membrane (i.e., rupture and detachment) develop. Abnormal hexagonal-shaped keratocytes and their apoptosis are the signs of endothelial dystrophy. The lack of analogs in domestic ophthalmology encouraged the scientists of Ufa Eye Research Institute to develop a device for corneal collagen crosslinking. The parameters of ultraviolet (i.e., wavelength, exposure time, power) to achieve the desired effect were identified. The specifics of some photosensitizers in the course of the procedure were studied. UFalink, a device for UV irradiation of cornea, and photosensitizer Dextralink were developed and adopted. Due to the high risk of endothelial damage, this treatment is contraindicated in severe keratoconus (CCT less than 400 microns). Major effects of corneal collagen crosslinking are the following: Young’s modulus (modulus of elasticity) increase by 328.9 % (on average), temperature tolerance increase by 5°C, and collagen fiber diameter increase by 12.2 % (anterior stroma) and 4.6 % (posterior stroma). In mild bullous keratopathy, corneal crosslinking provides antimicrobial effect. In moderate and severe keratopathy, crosslinking reduces pain and corneal edema and improves visual acuity immediately after the procedure. A case of HSV keratitis exacerbation was described. Amongst the complications, infection, halos, and posterior segment damage should be mentioned. Poor refractive results can be improved by the implantation of intrastromal corneal ring segments.